EVALUATING THE EFFECT OF FINANCIAL LITERACY ON INVESTMENT DECISION- META-ANALYSIS (Lex localis - Journal of Local Self-Government, 2025)
This meta-analysis investigates the impact of financial literacy on investment decision-making by synthesizing evidence from 30 peer-reviewed studies published between 2018 and 2024 thorugh Scopus Database. The dataset was retreived and drawn from a diverse sample including young, individual, household, and Small Medium Entrerprises (SME) investors, the analysis employs a random-effects model using Fisher’s r-to-z transformation. The resutls of the study indicate a statistically significant positive correlation between financial literacy and investment decisions with high heterogenity. The moderation analysis revealed no statistical significant influence of population type or publication year on the examined relationship. The findings of the study also confirmed that financial literacy sustaintially enhance the investment behaviour of invidiuals in promoting diversification, informed decision making, and lead to active particiaption in the financial markets. Therefore, the results underscore the importance of integrating financial education policy frameworks, especially for digitally active and younger populations to foster the vibrant investment practices in the economy through evolving financial landscape.